Rivers:a very short introduction - Moddleton, Nick (Oxford, 2012)
Rivers have played an extraordinarily important role in creating the world in which we live. They create landscapes and provide water to people, plants and animals, nourishing both town and country. The flow of rivers has enthused poets and painters, explorers and pilgrims. Rivers have acted as cradles for civilization and agents of disaster; a river may be a barrier or a highway, it can bear trade and sediment, culture and conflict. A river may inspire or it may terrify. This Very Short Introduction is a celebration of rivers in all their diversity. Nick Middleton covers a wide and eclectic range of river-based themes, from physical geography to mythology, to industrial history and literary criticism. Worshipped and revered, respected and feared, rivers reflect both the natural and social history of our planet. ABOUT THE SERIES: The Very Short Introductions series from Oxford University Press contains hundreds of titles in almost every subject area. These pocket-sized books are the perfect way to get ahead in a new subject quickly. Our expert authors combine facts, analysis, perspective, new ideas, and enthusiasm to make interesting and challenging topics highly readable.
Keywords: Rivers